The Power of Rapid Reviews for Bridging the Knowledge-to-Action Gap in Evidence-Based Virtual Health Care - Megan MacPherson; Sarah Rourke (JMIR Publications, 2024)
Despite the surge in popularity of virtual health care services as a means of delivering health care through technology, the integration of research evidence into practice remains a challenge. Rapid reviews, a type of time-efficient evidence synthesis, offer a potential solution to bridge the gap between knowledge and action. This paper aims to highlight the experiences of the Fraser Health Authority's Virtual Health team in conducting rapid reviews. This paper discusses the experiences of the Virtual Health team in conducting 15 rapid reviews over the course of 1.5 years and the benefit of involving diverse stakeholders including researchers, project and clinical leads, and students for the creation of user-friendly knowledge products to summarize results. The Virtual Health team found rapid reviews to be a valuable tool for evidence-informed decision-making in virtual health care. Involving stakeholders and focusing on implementation considerations are crucial for maximizing the impact of rapid reviews. Health care decision makers are encouraged to consider implementing rapid review processes to improve the translation of research evidence into practice, ultimately enhancing patient outcomes and promoting a culture of evidence-informed care.